Development of Ligase-Assisted Spacer Addition for the Measurement of Microsatellites. (July 2001) - Brockhurst, V.; Barnard, R.; Wolter, L.; Giffard, P.; Timms, P.
Conventional methods for detecting differences in microsatellite repeat lengths rely on electrophoretic fractionation on long denaturing polyacrylamide gels, a time-consuming and labor-intensive method. Therefore, there is a need for the development of new and rapid approaches to routinely detect such length polymorphisms. The advent of techniques allowing the coupling of DNA molecules to solid surfaces has provided new prospects in the area of mutation detection. We describe here the development and optimization of the ligase-assisted spacer addition (LASA) method, a novel and rapid procedure based on an ELISA format to measure microsatellite repeat lengths. The LASA assay was successfully applied to a set of 11 bird samples to assess its capabilities as a genotyping method.